USING SENTINEL-2A DERIVED CMRI FOR MANGROVE COVER MAPPING OVER 7 YEARS (2016-2022) IN QUANG YEN, QUANG NINH PROVINCE - Duy Quang, Pham; Phommachaly, Sounthala; Hai Hoa, Nguyen (Journal of Forestry Science and Technology, 2023)
Mangrove forests are intertidal wetlands and found along tropical, subtropical, and warm-temperate coastlines. They have vital functions in preventing coastal erosion, mitigating effects of wave actions, and protecting coastal habitats. However, mangrove forests are more likely to be vulnerable as typhoons frequently hit and under driving human pressures. The study has constructed the spatial distribution of mangrove cover from 2016 to 2022 by using Sentinel-2A imageries. The Sentinel-2A data were used to detect changes in the extent of coastal mangrove forests using the visual interpretation approach in combination with the CMRI thresholds defined (CMRI > 0.47 for mangrove forests, -0.25 < CMRI ≤ 0.47 for non-mangrove forests, and CMRI ≤ -0.25 for areas covered water). The overall accuracy assessments of land covers in each selected year (2016, 2017, 2018, 2019, 2020, 2021, and 2022) are greater than 93.0% with Kappa coefficient more than 0.89, which have clearly confirmed using Sentinel-2A data for mapping temporal changes in mangrove forests are very reliable in along the coast of Quang Yen. The study also showed that mangrove cover in Quang Yen town decreased by 343.7 ha in 2022 (2,765.4 ha) compared to 2016 (3,109.1 ha). The development of aquaculture and shrimp farming, the expansion of agricultural production, and other land uses were defined as the main drivers for mangrove deforestation during the period of 2016-2022. The study highly suggests that using Sentinel-2A imagery should be applied to assess the changes of mangrove cover in Quang Yen town and expanded in other similar coastal areas in Quang Ninh province toward sustainable mangrove management.